2023
DOI: 10.1108/cg-11-2022-0462
|View full text |Cite
|
Sign up to set email alerts
|

The same network auditor, family business groups and earnings manipulation: an evidence from emerging market

Abstract: Purpose This paper aims to examine whether family business groups’ (FBG) having the same network auditor among their affiliates mitigates earnings manipulation (EM). Design/methodology/approach This paper used unbalanced panel data from the years 2010–2019. The sample of the study is composed of 327 nonfinancial listed Pakistan Stock Exchange firms, consisting of 187 FBG-affiliated firms and 140 nonaffiliated firms. The ordinary least square and generalized least square regressions have been used to check th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 59 publications
0
7
0
Order By: Relevance
“…In the related literature, BIG4 audit firms are considered one of the most important determinants of EM, which mitigates EM. The study (Khan and Kamal, 2023), which looked at Pakistan, Khan and Kamal (2023) found. Moreover, these results are in line with Abid et al (2018), who reported that BIG4 audit firms are not effective in Pakistan, as they are not operating in Pakistan under their real brand name but rather under local affiliates.…”
Section: 43mentioning
confidence: 98%
See 4 more Smart Citations
“…In the related literature, BIG4 audit firms are considered one of the most important determinants of EM, which mitigates EM. The study (Khan and Kamal, 2023), which looked at Pakistan, Khan and Kamal (2023) found. Moreover, these results are in line with Abid et al (2018), who reported that BIG4 audit firms are not effective in Pakistan, as they are not operating in Pakistan under their real brand name but rather under local affiliates.…”
Section: 43mentioning
confidence: 98%
“…The ability to effectively control EM and enhance the quality of financial reports requires the BOD's accounting knowledge (financial expertise), which is essential to the BOD's monitoring role (Siam et al, 2014). Moreover, in Pakistan, there is a dominance of insiders and family directors in the boards of PSX-listed firms; as reported by Khan (2023), there is a majority of family directors in the boards of PSX-listed firms, and every third member in PSX-listed firms is a family member. Therefore, due to the importance of independent and expert members in the boards, their inclusion in the board and AC was made mandatory in Pakistan via CCG-2017.…”
Section: Board Expertise and Earnings Manipulationmentioning
confidence: 99%
See 3 more Smart Citations